Imagery of ritual actions in religious dreaming: steps toward a theory and method of the cognition of dreamt ritual interaction - Nordin, Andreas (Religion, 2024)
The research literature on religious dreaming demonstrates the commonness of supernatural agent (SA) imagery, as well as various ritualistic and divinatory uses of dream content in the waking state. Less well mapped is the related domain of dream imagery about rituals (DIR). This article aims to provide a survey and analysis of DIR items and interactions in line with dream and ritual theories, with case illustrations from dream reports based on ethnographic fieldwork among Hindus in Nepal. The analysis relies on an understanding of “ritual” based on their assumed “obvious aspects” and traits, and on theoretical assumptions drawn from cognitive and evolutionary accounts of ritualization in relation to prominent strands in dream research such as threat simulation theory, and social simulation theory. The aim is to develop a novel strategy for exploring imagined ritual traits in dreaming. This undertaking contributes to the methodology and theoretical understanding of religious dream cognition.